2016
DOI: 10.1177/0956462416665942
|View full text |Cite
|
Sign up to set email alerts
|

Histoplasmosis mimicking non-Hodgkin lymphoma in a 40-year-old man with AIDS

Abstract: In patients with acquired immunodeficiency syndrome (AIDS), advanced immunosuppression is associated with atypical presentation of dermatological conditions. Our patient presented with a single crusted plaque over the lower lip and large tender cervical lymphadenopathy. The enzyme-linked immunosorbent assay for human immunodeficiency virus was found to be positive, and his CD4+ lymphocyte cell count was 4 cells/mm. The presence of multiple histoplasma spores in the biopsies from the crusted plaque over lip and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…3,4,6 Asymptomatic adrenal involvement has been described in 30 to 50% of patients with disseminated histoplasmosis and henceforth a meticulous work-up with close follow-up is necessary as there is no clinical diagnostic hallmark of the disease; often, they mimic visceral leishmaniasis, which is prevalent in this part of India, and the diagnosis is often missed. [17][18][19] Increased steroid concentration within the adrenal glands may promote the growth of H. capsulatum, as suggested by some researchers. 20 The histoplasmosis cases from India are based on the study by Randhawa and Gugnani who found a total of 426 cases (1954-2018) and 207 cases from the literature search (2018-2020; excluding studies cited in Randhawa and Gugnani).…”
Section: Discussionmentioning
confidence: 99%
“…3,4,6 Asymptomatic adrenal involvement has been described in 30 to 50% of patients with disseminated histoplasmosis and henceforth a meticulous work-up with close follow-up is necessary as there is no clinical diagnostic hallmark of the disease; often, they mimic visceral leishmaniasis, which is prevalent in this part of India, and the diagnosis is often missed. [17][18][19] Increased steroid concentration within the adrenal glands may promote the growth of H. capsulatum, as suggested by some researchers. 20 The histoplasmosis cases from India are based on the study by Randhawa and Gugnani who found a total of 426 cases (1954-2018) and 207 cases from the literature search (2018-2020; excluding studies cited in Randhawa and Gugnani).…”
Section: Discussionmentioning
confidence: 99%